Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan PT. Ramayana Lestari Sentosa Tbk Cabang Samarinda Central Plaza (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of work discipline on employee performance at PT. Ramayana Lestari Sentosa Tbk Samarinda Central Plaza Branch. The background of this study stems from the importance of work discipline in improving the effectiveness and productivity of human resources as the main asset of an organization. This study employs a quantitative approach using a survey method, distributing questionnaires to 127 employees as respondents. Data were analyzed using simple linear regression. The results indicate that work discipline has a positive and significant impact on employee performance. Employees with high levels of discipline tend to demonstrate punctuality, compliance with rules, and responsibility in performing tasks, thereby contributing to improved performance. These findings imply that companies need to continue strengthening work discipline culture as a strategy for improving performance. This study also contributes theoretically to the development of human resource management science and practically serves as a basis for formulating managerial policies focused on enhancing employee discipline and productivity.